Bentuk Pertunjukan Drama Tari Bejoraq - Ashwan Kailani; Hary Murcahyanto; Mariadah Mariadah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
This study aimed to to describe the element of performance form and the meaning of the motion of the drama "bejoraq" in the Marong village Praya Timur, Lombok Tengah Regency. There were also data collection techniques carried out in this study by conducting observations, interviews, and documentation. This research was a descriptive qualitative research by taking all samples supporting this study. The data analysis technique used consists of four stages such as data collection data reduction, data display, and conclusion drawing/ verification The dominant theory used in this study was a theory about the form of art performance that is shown to be shown can be exhibitions, dance, puppets, music, drama, and so on. From the results and discussion it was concluded that the form of the Bejoraq drama show has several elements that strengthen performances such as motion, costumes, makeup, dialogue, music, stage, lighting, and the theme of the show. Keywords: Form of Performance, Dance drama, "Bejoraq".